Why we fall apart engineering's reliability theory explains human aging. - Gavrilov, L. (IEEE spectrum)
The quest to understand and control aging has led two biologists to draw inspiration from what might seem an unlikely source: reliability engineering. The engineering approach to understanding aging is based on ideas, methods, and models borrowed from reliability theory. The theory is so general in scope that it can be applied to understanding aging in living organisms as well. In the ways that we age and die, we are not so different from the machines we build. The difference is minimized if we think of ourselves in this unflattering way: we are like machines made up of redundant components, many of which are defective right from the start. Human aging provides a common scientific language and general framework for scientists working in different areas of aging research. It helps them knock down the barriers that specialists have constructed and allows them to understand each other better. At the start of a machine's life, the working-in period, failure rates are high; they then decrease with age. The same working-in period exists early in life for most living organisms, including humans; for humans, it is called the infant-mortality period of mortality. In humans, the aging period occurs approximately from the ages of 20 to 100 years of mortality. The observation that the relative differences in mortality between populations tend to decrease with age; also known as mortality convergence in later life. The positive effect of redundancy in systems is tolerance of damage, which decreases the initial risk of failure (death) and increases life span. Another aging rule becomes apparent in studies of the older end of the population. Indeed, in contrast to technical devices, which are constructed out of previously manufactured and tested components, organisms form themselves through a process of self-assembly out of untested elements cells. In other words, machines can be made to avoid faults, while living things make themselves to tolerate faults This fundamental difference in the manner in which people and machines are made has important consequences for how they age. If we accept the idea that we are born with a large amount of damage, it follows those even small improvements to the processes of early human development ones that increase - the numbers of initially functional elements could result in a remarkable fall in mortality and a significant extension of human life. Indeed, there is mounting evidence now in support of the idea of fetal origins of adult degenerative diseases and early-life programming of aging and longevity. Scientists have been studying what's called the hormesis effect, the observation that a little bit of poison activates an organism's self-repair mechanisms, having the side effect of protecting it against other hazards than the poison itself. Reliability theory suggests that there might be no single underlying aging process. Instead, aging may be largely an emergent property of redundant systems. Such systems can have a network of destruction pathways, each associated with particular manifestations of aging, whether menopause or Alzheimer's disease.